2010
DOI: 10.1183/09031936.00106109
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diet and asthma and atopy at 8 years of age: the PIAMA birth cohort study

Abstract: Diet may affect the development of asthma. We investigated whether asthma or atopy outcomes at 8 yrs of age were associated with long-term dietary exposure, and whether associations were different for consumption at early or later age.The Prevention and Incidence of Asthma and Mite Allergy (PIAMA) birth cohort enrolled 4,146 participants at baseline, who were followed up to 8 yrs of age. Dietary intakes of interest were fruit, vegetables, brown/wholemeal bread, fish, milk, butter and margarine. Associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 33 publications
4
55
1
3
Order By: Relevance
“…In contrast, Willers et al showed no association between the amount of fish consumption at age 2 to 3 years and 7 to 8 years and asthma diagnosis at 8 years. 33 Age differences and variation in measuring fish consumption make it difficult to compare our results with previous studies but there seems to be a tendency for a beneficial effect on asthma when fish exposure occurs in the first year of life. Our study suggests that appropriate timing of introduction of fish rather than the amount of fish servings after 12 months is important in the association with wheezing.…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast, Willers et al showed no association between the amount of fish consumption at age 2 to 3 years and 7 to 8 years and asthma diagnosis at 8 years. 33 Age differences and variation in measuring fish consumption make it difficult to compare our results with previous studies but there seems to be a tendency for a beneficial effect on asthma when fish exposure occurs in the first year of life. Our study suggests that appropriate timing of introduction of fish rather than the amount of fish servings after 12 months is important in the association with wheezing.…”
Section: Discussioncontrasting
confidence: 52%
“…refused. 4 Moreover, high consumption of antioxidants was associated with higher pulmonary function and decreased chronic respiratory symptoms in children, especially those exposed to high levels of air or smoke pollutants. 7,8,29,30 Fish consumption has been also related with lower asthma episodes in infancy and childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of antibiotic treatment (Droste et al, 2000;Verhulst et al, 2008) as well as the change in lifestyle in westernized countries (Matricardi, 2001), especially including diet (Chatzi et al, 2007;Willers et al, 2011), can lead to alterations in the microbial composition and such conditions are strongly linked to a higher risk of asthma development (Bottcher et al, 2000). Specific shifts in the intestinal microbial communities have been associated with an asthmatic phenotype, displaying a reduction in Bacteroidetes, Lactobacilli and Bifidobacteria (Bjorksten et al, 1999;Ouwehand et al, 2001).…”
Section: Asthmamentioning
confidence: 99%